2017
DOI: 10.1002/jcp.25516
|View full text |Cite
|
Sign up to set email alerts
|

DJ‐1/Park7 Sensitive Na+/H+ Exchanger 1 (NHE1) in CD4+ T Cells

Abstract: DJ-1/Park7 is a redox-sensitive chaperone protein counteracting oxidation and presumably contributing to the control of oxidative stress responses and thus inflammation. DJ-1 gene deletion exacerbates the progression of Parkinson's disease presumably by augmenting oxidative stress. Formation of reactive oxygen species (ROS) is paralleled by activation of the Na /H exchanger 1 (NHE1). ROS formation in CD4 T cells plays a decisive role in regulating inflammatory responses. In the present study, we explored wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…NHE1 expression and Na + /H + exchanger activity are highly sensitive to oxidative stress [17, 21]. Na + /H + exchanger activity in turn impacts on NADPH oxidase activation and generation of reactive oxygen species [17].…”
Section: Discussionmentioning
confidence: 99%
“…NHE1 expression and Na + /H + exchanger activity are highly sensitive to oxidative stress [17, 21]. Na + /H + exchanger activity in turn impacts on NADPH oxidase activation and generation of reactive oxygen species [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely triggered by the elevated proliferation of DJ-1 deficient CD3 + T cells and enhanced migration in response to stromal cell-derived factor-1 via overexpression of chemokine receptor 4 (13,85). In addition, a new relationship between the DJ-1-ROS-Na + /H + exchanger 1 (NHE1) revealed that DJ-1-deficient CD4 + T cells upregulated the expression and activity of NHE1, which may have resulted from enhanced ROS generation (86). In turn, NHE1 activity can impair ROS production (86).…”
Section: Dj-1 and Asmentioning
confidence: 99%
“…In addition, a new relationship between the DJ-1-ROS-Na + /H + exchanger 1 (NHE1) revealed that DJ-1-deficient CD4 + T cells upregulated the expression and activity of NHE1, which may have resulted from enhanced ROS generation (86). In turn, NHE1 activity can impair ROS production (86). In this respect, lack of DJ-1 promotes neointima formation since NHE1 contributes to cell migration (87).…”
Section: Dj-1 and Asmentioning
confidence: 99%
“…The authors suggested that the DJ1-C57 model effectively recapitulates the early stages of PD and allow study of the preclinical aspects of neurodegeneration 14 . Our own studies with DJ-1 −/− mice also suggested that DJ-1 protein is involved in the regulation of adaptive immune CD4 + T cells and their development and functions by modifying of sodium hydrogen exchanger 1 (NHE1) and ROS formation 15,16 . One should keep in mind that different DJ-1 −/− mice lines with different background could be more or less prone to develop neurodegeneration and in additive to genetic changes additional environmental and unknown factors may play a crucial role for the disease development in DJ-1 −/− mice.…”
mentioning
confidence: 90%